Media Video Bimbingan "Mari Berteman" sebagai Layanan Informasi untuk Mencegah Cyberbullying di Sekolah Menengah Kejuruan - Rayhana, Zul Asfi; Farida Aryani; Sahril Buchori (Technocouns: Journal of Technology in Guidance and Counseling, 2025)
This research developed the guidance video media "Let's Be Friends" as cyberbullying information to prevent cyberbullying in vocational high schools. The aim of this research is to; 1) To find out the description of the need for media products, 2) To find out the prototype of the guidance video media product, 3) To find out the level of validity of the media product, 4) To find out the level of practicality of the guidance video media product. This research uses the ADDIE model. The instruments used in this research were questionnaires and interview guidelines. Based on the research results, it shows that; 1) Students of SMK Negeri 2 Sidrap still carry out cyberbullying in the school environment, so media such as the "Let's Be Friends" guidance video media are very necessary to support the implementation of information services; 2) The media prototype of the "Let's Be Friends" Guidance Video consists of an opening, introduction, content, conclusion; 3) The assessment of guidance video media is carried out by material experts and media experts with very good criteria. Assessment by teachers obtains scores from three aspects, namely usefulness, feasibility and accuracy, with very valid criteria. In conclusion, the level of validity of the "Let's Be Friends" guidance video media as a valid cyberbullying information service for students to use, so that the media is worthy of extensive testing